Factores de riesgo en adultos mayores con enfermedades crónico-degenerativas no transmisibles de la parroquia Quinara - Salazar Ontaneda, Vivian Yuleisi (2023)
The most common non-communicable chronic-degenerative diseases are diabetes, obesity, cancer, HTA; same that over time degrade physical-mental health and even lead to complications that cause death, especially in older adults due to aging and risk factors. The objective of this study was to determine the sociodemographic characteristics and modifiable risk factors associated with non-communicable chronic-degenerative diseases in the elderly of the Quinara parish, in order to design health promotion actions, it was a descriptive study. , quantitative, of a cross-sectional cohort, with a sample of 78 older adults to whom an instrument made up of 26 questions was applied prior to the delivery of informed consent; the presentation of the results was done through tables; The results are: sociodemographic and health characteristics, it stands out that the age is in a range of 71 to 80 years with 42%, being the female sex with 64% the greatest carrier of these pathologies, 73% are married, 58% have reached a level of primary education, 51% work as a housewife and 29% in agriculture and the pathology that stands out is HTA with 62%; on the other hand, the prevailing results on modifiable risk factors is that the total population has adequate medical control, of which 93% take medication, 84% feel satisfied with their lives, 77% have not suffered from any personal problem, 96% consume three to five meals/day, 63% maintain inadequate consumption of food groups, 50% consume the same variety of foods every day, 76% perform physical activity in thirty minutes, 91% do not smoke and 85% do not drink alcohol; finally, based on the results, there is little possibility that they trigger complications, therefore, this research developed an educational proposal aimed at improving the state of health in these factors. It is concluded that there are few modifiable risk factors which are altered